Global And Regional Effects On Sectoral Returns Volatility Among Gulf Cooperation Council(Gcc) Countries - Mustafa, Makwan Jamil (2022)
Due to the mono-dependence on oil in the Gulf Cooperation Council (GCC) countries, any volatilities or shocks in the oil sector may undermine investment opportunities between and within sectors. While there has been much research on the portfolio of stock return, there are fewer empirical studies on volatility spillover in stock markets at the disaggregated level. There is also a theoretical gap in volatility spillover between intra and inter-sectoral returns. Since there is extending theoretical evidence in volatility literature, it is crucial to examine the interdependency among intra and intersectoral returns at three different levels. These levels include domestic, regional, and international stock markets. Investigating these three levels is immensely vital. First, it would be prudent to investigate the intra-volatility spillover effect among the sectoral returns in each GCC country. Second, you ought to examine the GCC regional-volatility spillover effect on the sectoral returns in each GCC country. Third, you must assess the global-volatility spillover effect on the sectoral returns in each GCC country.